Exogenous 24-epibrassinolide mitigates damage in grape seedlings under low-temperature stress - Dong, Fengxia; Li, Xinyu; Liu, Chang; Zhao, Boxiang; Ma, Yu; Ji, Wei (Frontiers in Plant Science, 2025)
Grapes are cultivated worldwide and have a high economic value as fruit trees. However, winter frost damage and spring cold damage have limited the sustainability of the table grape industry. A novel plant growth regulator, 24-epibrassinolide (EBR), exhibits an essential regulatory function in plant life cycles, especially in its unique mechanism against various environmental stresses. We treated ‘Lihongbao’ grapes with exogenous EBR (0.2 μM), brassinazole (BRZ, 10 μM), EBR + BRZ (0.2 μM +10 μM), and deionized water (CK). We investigated the effect of exogenous EBR on ‘Lihongbao’ grape seedlings under low-temperature stress (4°C) at different periods (0 h, 12 h, 24 h, 48 h, and 96 h). We explored physiological mitigation mechanisms of exogenous EBR in grape seedlings with low-temperature injury by observing the impacts of EBR treatment on the physical and biochemical indices such as phenotypes and anatomical structures, photosynthetic characteristics, chlorophyll fluorescence parameters, antioxidant systems, and osmoregulatory substances. Exogenous EBR had an inhibitory effect on cold stress in grape seedlings at different treatment periods compared with the CK group. Based on plant phenotype and anatomical structure, the leaves of the grape seedlings treated with exogenous EBR showed no signs of water loss or wilting. At 96 h under low-temperature stress, the lower epidermal thickness (LET), palisade tissue thickness (PT), palisade-to-sea ratio (P/S), and blade structural compactness (CTR) of the exogenous EBR-treated grape leaves were significantly reduced by 6.71%, 19.59%, 14.52%, and 11.65% compared with the CK group, respectively. Chlorophyll a (Chl a), chlorophyll b (Chl b), total chlorophyll (Chl total), carotenoids (carotenoid), transpiration rate (Tr), and stomatal conductance (Gs) contents of exogenous EBR-treated grape leaves were significantly upregulated by 30.24%, 48.52%, 39.75%, 34.67%, 704.66%, and 277.27%, respectively. The intercellular CO2 concentration (Ci) and non-photosynthetic burst coefficient (NPQ) of exogenous EBR-treated grape leaves were significantly downregulated by 16.29% and 25.83%, respectively. Glutathione (GSH) contents of exogenous EBR-treated grape leaves were significantly upregulated by 33.63%, superoxide dismutase (SOD), peroxidase (POD), and ascorbate peroxidase (APX) activities of exogenous EBR-treated grape leaves were significantly increased by 42.70%, 27.60%, and 28.64%, respectively. However, hydrogen peroxide (H2O2), superoxide anion (O2·−), and malondialdehyde (MDA) contents of exogenous EBR-treated grape leaves were reduced by 29.88%, 23.66%, and 47.96%, respectively, and significantly. Catalase (CAT) activity of exogenous EBR-treated grape leaves significantly increased by 15.03%. Soluble sugar and free proline contents increased by 5.29% and 19.44%, respectively, and significantly. Exogenous EBR could effectively alleviate growth inhibition caused by regulating the antioxidant system indices in grape seedlings under cold temperature. The results offer a theoretical basis for enhancing grape cold tolerance.